Female Characters' Resistance to Domestication in the Netflix Film Gadis Kretek Series, Simone de Beauvoir's Feminism Studies - Nur Annisa Miftachul Jannah; Firly Annisa (Jogjakarta Communication Conference (JCC), 2024)
The Gadis Kretek series on Netflix (2023) emerged as a phenomenal show upon its debut in November 2023. This series, an adaptation of Ratih Kumala's novel "Gadis Kretek" (2012), showcases the journey of the main character, Dasiyah, as she endeavors to break free from the constraints of patriarchy amidst the backdrop of 1960s Indonesian political turmoil. Dasiyah's character consistently challenges the societal norms that confine her as a woman. This research seeks to identify the various forms of resistance displayed by female characters against domestication, drawing upon Simone de Beauvoir's feminist theories. The primary source material for this study is the Netflix series "Gadis Kretek," analyzed through qualitative methods and cinematographic techniques. Findings reveal instances of social injustice perpetrated against female characters through domestication. Resistance among these characters manifests in rejecting arranged marriages, refusing subordination, pursuing employment, and boldly advocating for their romantic interests. Thus, this research contributes to understanding the imperative of resisting domestication, particularly for women.